Heating slurry adaptive to glass substrate atomizing core, preparation of heating slurry and application of heating slurry in electronic cigarette and atomizing core
By adjusting the component ratio of the heating slurry, the problems of low heating efficiency of the electronic cigarette atomization core and poor stability of the glass substrate are solved, and the effects of high thermal stability and high thermal efficiency are achieved, ensuring the film integrity and safety of the glass substrate sex.
Patent Information
- Application Number
- CN202411191159.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
The heating slurry of the existing electronic cigarette atomization core is difficult to adapt to the heating rate requirements, which can easily lead to cracking of the glass substrate, unsatisfactory high-temperature stability and physical chemical performance, and layering of the coating line.
A heating slurry including 5 to 35 parts by weight of the dispersion, 50 to 105 parts by weight of metal powder, 0.5 to 15 parts by weight of glass powder, and 0.1 to 15 parts by weight of additives, and the dispersion contains an organic solvent. and resin, metal powder is silver powder and palladium powder, glass powder is lead-free borosilicate glass powder, and additives are mullite, zirconium dioxide or beryllium oxide. High thermal stability and high heating efficiency are achieved by adjusting the component ratio.
It achieves stable physical and chemical properties at high temperatures, avoids the release of harmful substances, perfectly coated with the glass substrate, conforms to the thermal expansion coefficient, and has high heating efficiency under low power conditions.
Smart Images

Figure CN119111862A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electronic cigarette atomization cores, and in particular to the field of electronic cigarette atomization core resistance heating sheets and slurries thereof suitable for glass substrates. Background Art
[0002] In the electronic cigarette atomizer device, the atomizer core assembly is the core component of the electronic cigarette atomizer device. Its main function is to atomize the liquid tobacco oil into smoke at high temperature through the principle of heating by the atomizer core when the user uses it, and then send it to the consumer's mouth through a special smoke channel to replace traditional tobacco, allowing consumers to experience a new smoking pleasure. The electronic cigarette atomizer core is composed of a heating wire and an oil guide component. The oil guide substrate has evolved from the earliest porous metal nickel mesh and steel wire mesh to the later glass fiber rope, polyester fiber rope, cotton fiber rope, and the porous ceramic core oil guide, which has been a hot research and development hotspot in recent years.
[0003] The above materials all have some hidden dangers that need to be improved during consumer use: the nickel element of the metal nickel mesh has a migration hazard, and the surface is easily carbonized and blackened after heating, which affects the user experience and has low oil conduction efficiency. Glass fiber rope is easily decomposed by heat, which is harmful to human tissue, and is easy to carbonize and coke, affecting the taste, easy to break, and inconvenient to fix at both ends. Cotton fiber rope, also known as organic cotton rope, does not contain chemical fibers and additives, and has a fast oil absorption speed, but cotton fiber is easy to dry burn, and is prone to core sticking and falling off, which can easily cause damage to the human body and pose a fire hazard. Ceramic oil-conducting material uses its porous structure to conduct oil instead of existing fiber ropes, that is, porous ceramics, which have the advantages of high temperature resistance, long life, and safety; however, the disadvantage of ceramic oil conduction is that the rate is low, which affects the amount of smoke, and it is also easy to dry burn and lose powder, and the cost price is relatively high.
[0004] In the prior art, the electronic cigarette atomization device with porous glass as the substrate solves the above problems existing in ceramic cores, cotton cores, etc. However, the existing heating paste often requires high power, insufficient heating rate, and is prone to cracking of the glass substrate and delamination of the film circuit. Summary of the invention
[0005] In view of the problems that existing heating slurries are difficult to adapt to the heating rate requirements of electronic cigarettes, easily cause glass cracking, have unsatisfactory high-temperature stability and physical and chemical properties, and stratification of coated circuits, the present invention provides a heating slurry adapted to a glass-based atomization core and the heating slurry thereof, aiming to provide a heating slurry that is adapted to the application requirements of electronic cigarette atomization cores and can improve their heating efficiency at low power and high-temperature stability.
[0006] The second object of the present invention is to provide a method for preparing the heat-generating slurry.
[0007] The third object of the present invention is to provide a glass substrate atomizing core coated with the heat-generating slurry and solidified.
[0008] The fourth object of the present invention is to provide a method for preparing the glass substrate atomizing core.
[0009] A fifth object of the present invention is to provide an electronic cigarette comprising the glass substrate atomization core.
[0010] Heating slurries are widely used, but different application scenarios and different adaptable substrates need to face completely different technical problems. For example, for the glass-based electronic cigarette atomization core of the present invention, it needs to solve the unique problems of slow heating efficiency, mismatch with the expansion performance of the glass substrate, cracking and peeling of the coating during the heating and atomization stage, and unsatisfactory atomization effect and high-temperature stability. In view of this problem, it is difficult to reasonably adapt the conventional heating slurry. In view of this problem, the present invention has provided the following solutions after in-depth research:
[0011] A heating slurry suitable for a glass substrate atomizing core, comprising 5 to 35 parts by weight of a dispersion, 50 to 105 parts by weight of metal powder, 0.5 to 10 parts by weight of glass powder, and 0.1 to 15 parts by weight of an additive;
[0012] Wherein, the dispersion comprises an organic solvent and a resin;
[0013] The metal powder includes silver powder and palladium powder;
[0014] The glass powder is lead-free borosilicate glass powder with a softening point of 600-700°C;
[0015] The auxiliary agent includes at least one of mullite, zirconium dioxide or beryllium oxide.
[0016] In the present invention, synergy can be achieved through the joint control of the components and proportions in the slurry, so that the heat-generating slurry can have high thermal stability, and can have stable physical and chemical properties at high temperatures, release no harmful substances, and can be perfectly coated with the glass substrate, match the thermal expansion coefficient of the glass substrate, and have high heating efficiency under low power conditions.
[0017] In the present invention, in the dispersant, the resin is selected from at least one of acrylic resin, polymethacrylic resin, rosin resin, phenolic resin, cellulose resin or polyurethane resin; preferably at least one of cellulose resin and acrylic resin.
[0018] In the present invention, the cellulose resin is selected from at least one of ethyl cellulose, methyl cellulose, hydroxymethyl cellulose and carboxymethyl cellulose, preferably ethyl cellulose.
[0019] In the present invention, the organic solvent is selected from at least one of diethylene glycol butyl ether acetate, DBE mixed solvent, ethyl acetate, dioctyl phthalate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether, terpineol or tributyl citrate; preferably at least one of diethylene glycol butyl ether acetate, DBE mixed solvent or ethyl acetate.
[0020] In the present invention, the mass percentage of the resin in the dispersion can be adjusted as needed, for example, it can be 1 to 70%, further can be 5 to 50%, and further can be 10 to 20%.
[0021] In the present invention, in the metal powder, the silver powder is 50 to 90 parts, further can be 60 to 80 parts, further can be 65 to 75 parts; the palladium powder is 2 to 15 parts, further can be 3 to 10 parts, further can be 4 to 8 parts.
[0022] In the present invention, the silver powder includes at least two of spherical silver powder with a first particle size, spherical silver powder with a second particle size, or flaky silver powder with a third particle size.
[0023] In the present invention, the first particle size spherical silver powder has a particle size of 0.8-2 μm and a tap density of 3-5 g / ml; the second particle size spherical silver powder has a particle size of 100-550 nm and a tap density of 4-6 g / ml; the third particle size flake silver powder has a particle size of 0.5-1.5 μm and a tap density of 5-7 g / ml.
[0024] In the present invention, the silver powder includes spherical silver powder of the first particle size and spherical silver powder of the second particle size; the mass ratio of the spherical silver powder of the first particle size to the spherical silver powder of the second particle size is (30-70):(10-30), preferably (45-60):(10-25).
[0025] Furthermore, the silver powder includes spherical silver powder of the first particle size and flake silver powder of the third particle size; the mass ratio of the spherical silver powder of the first particle size to the flake silver powder of the third particle size is (30-70):(10-30), preferably (50-65):(10-20).
[0026] Furthermore, the silver powder includes spherical silver powder of a first particle size, spherical silver powder of a second particle size and flaky silver powder of a third particle size, and the mass ratio of the three is (40-70):(5-30):(5-20).
[0027] In the present invention, the softening point temperature of the glass powder may further be 650±20° C. The particle size of the glass powder is 0.8 to 3 μm, preferably 1 to 2 μm.
[0028] In the present invention, the auxiliary agent comprises mullite.
[0029] In the present invention, the mullite comprises at least one of a first-size mullite with a particle size of 1 to 5 μm or a second-size mullite with a particle size of 50 to 500 nm.
[0030] Furthermore, the mullite includes mullite of a first particle size and mullite of a second particle size, wherein the mass ratio of the mullite of the first particle size to the mullite of the second particle size is (1-9):(1-2).
[0031] In the present invention, the heat generating paste comprises 5 to 30 parts by weight of a dispersion, 65 to 90 parts by weight of metal powder, 1 to 7 parts by weight of glass powder and 2 to 10 parts by weight of an auxiliary agent.
[0032] Furthermore, the heat generating paste comprises 10 to 20 parts by weight of a dispersion, 70 to 80 parts by weight of metal powder, 1 to 7 parts by weight of glass powder and 3 to 6 parts by weight of an auxiliary agent.
[0033] The heat-generating slurry of the present invention may further contain a surfactant.
[0034] In the present invention, there is no particular requirement for the type of the surfactant, and for example, the surfactant may include at least one of polyether siloxane or acrylate.
[0035] In the present invention, the weight portion of the surfactant is less than or equal to 5 parts, further less than or equal to 2 parts, and further can be 0.1 to 1 part.
[0036] The present invention also provides a method for preparing the heat-generating slurry suitable for a glass substrate atomizing core, which comprises obtaining a dispersion in advance and then mixing the components to obtain the slurry.
[0037] Furthermore, the dispersion preparation step is to heat the organic solvent to 50-90° C., add the resin, and stir to dissolve.
[0038] The present invention also provides an application of the heat-generating slurry adapted to the glass substrate atomizing core, which is compounded on a glass substrate and then cured to obtain;
[0039] In a preferred application, the glass substrate atomizer core is used to prepare an electronic cigarette.
[0040] The present invention further provides a glass substrate atomizing core, which comprises a glass substrate and a heating layer composited thereon, wherein the heating layer is formed by curing the heating slurry suitable for the glass substrate atomizing core according to the present invention.
[0041] The glass-based atomizing core of the present invention has a heating layer obtained by curing the heating slurry of the present invention, and other components and structures thereof can be conventional.
[0042] In the present invention, the curing temperature is, for example, 600 to 800°C, and may further be 650 to 750°C.
[0043] The curing time is not particularly limited, and may be, for example, 5 minutes or longer, and further may be 5 to 30 minutes.
[0044] The present invention also provides an electronic cigarette, which comprises the glass substrate atomization core of the present invention.
[0045] The electronic cigarette of the present invention, in addition to comprising the glass-based atomizing core of the present invention, may have conventional components and parts in addition.
[0046] Beneficial Effects
[0047] The present invention provides a synergistic heating slurry, which has high thermal stability, low dielectric loss factor and extremely low thermal expansion coefficient. While having stable physical and chemical properties at high temperatures and releasing no harmful substances, it can be perfectly coated with a glass substrate and match the thermal expansion coefficient of the glass substrate, and has high heating efficiency under low power conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The dry-burning temperature-time curve of the heating sheet made of the heating slurry in Example 2;
[0049] Figure 2 Data graph of the aspect ratio of the film measured for the heating sheet made in Example 2;
[0050] Figure 3 The appearance of the film observed by Zeta3D microscope after the heating sheet made in Example 2 was subjected to 300 atomization tests and 30 dry-burning tests;
[0051] Figure 4 The data graph of the aspect ratio of the film measured by Zeta3D microscope for the heating sheet made in Comparative Example 4;
[0052] Figure 5 The appearance of the film observed by Zeta3D microscope after the heating sheet made in comparative example 4;
[0053] Figure 6 The data graph of the aspect ratio of the film measured by Zeta3D microscope for the heating sheet made in Comparative Example 5;
[0054] Figure 7 The appearance of the film observed by Zeta3D microscope after the heating sheet made in comparative example 5;
[0055] Figure 8 The appearance of the film observed by Zeta3D microscope after the heating sheet made in comparative example 3;
[0056] Fig. 9 The appearance of the heating sheet made in comparative example 6 after coating;
[0057] Fig.10 Comparative Example 1 shows the appearance of the coating after the heating sheet was made and the dry-burning test was performed. DETAILED DESCRIPTION
[0058] In the following cases, the amounts mentioned are all by weight.
[0059] Unless otherwise stated, the particle size refers to the D50 particle size.
[0060] Example 1
[0061] A heating slurry suitable for a glass-based atomizer core, comprising: 15.5 parts of a dispersion, 5 parts of borosilicate glass powder (particle size 2 μm, glass softening point 650°C), 5 parts of an additive (mullite in this case, with a particle size of 3 μm), 0.5 parts of polyether siloxane, 4 parts of palladium powder, 55 parts of 1 μm spherical silver powder (first particle size silver powder particles), and 15 parts of 500 nm spherical silver powder (second particle size silver powder particles).
[0062] Preparation method:
[0063] S1: Heat 85 parts of diethylene glycol butyl ether acetate to 70°C, add 15 parts of ethyl cellulose, stir and dissolve, and prepare a dispersion.
[0064] S2: Take 15.5 parts of the dispersion, add 5 parts of borosilicate glass powder, 5 parts of mullite, 0.5 parts of polyether siloxane, 4 parts of palladium powder, 55 parts of 1 μm spherical silver powder, and 15 parts of 500 nm spherical silver powder in sequence, mix and stir, and grind and disperse on a three-roll mill to obtain a heating slurry.
[0065] Example 2
[0066] Compared with Example 1, the only difference is that the mass fractions of borosilicate glass powder and palladium powder are changed to 1 part of borosilicate glass powder and 8 parts of palladium powder respectively, and the other operations and parameters are the same as those in Example 1.
[0067] Example 3
[0068] Compared with Example 2, the only difference is that the auxiliary agent is replaced by beryllium oxide, and the other operations and parameters are the same as those in Example 1.
[0069] Example 4
[0070] Compared with Example 2, the only difference is that the auxiliary agent is replaced with zirconium dioxide, and the other operations and parameters are the same as Example 1.
[0071] Example 5
[0072] Compared with Example 2, the difference is that the silver powder composition is different and the dispersion composition is different. The silver powder includes spherical silver powder with a first particle size (1.5 μm) and flaky silver powder with a third particle size (1.0 μm); the mass ratio of the spherical silver powder with the first particle size to the flaky silver powder with the third particle size is 60:10. The dispersion includes 80 parts of DBE mixed solvent and 20 parts of acrylic resin (L990045).
[0073] Example 6
[0074] Compared with Example 2, the only difference is that the mass fraction of borosilicate glass powder is changed to 7 parts of borosilicate glass powder.
[0075] Example 7
[0076] Compared with Example 2, the only difference is that the composition of the auxiliary agent is changed. The auxiliary agent includes mullite with a particle size of 3 μm and mullite with a particle size of 100 nm, and the mass ratio of the two is 8:2.
[0077] Example 8
[0078] Compared with Example 2, the only difference is that the mass fractions of the dispersion and the mass fractions of the metal oxide are changed, namely, 10.5 parts of the dispersion and 10 parts of mullite.
[0079] Comparative Example 1
[0080] Compared with Example 2, the only difference is that the mass fraction of borosilicate glass powder is changed to 11 parts of borosilicate glass powder.
[0081] Comparative Example 2
[0082] Compared with Example 2, the only difference is that the mass fraction of borosilicate glass powder is changed to 0.1 parts of borosilicate glass powder.
[0083] Comparative Example 3
[0084] Compared with Example 2, the only difference is that the type of glass powder is changed to silicate glass powder.
[0085] Comparative Example 4
[0086] Compared with Example 2, the only difference is that the mass fraction of the auxiliary agent is changed to 16 parts of mullite.
[0087] Comparative Example 5
[0088] Compared with Example 2, the only difference is that no auxiliary agent is added.
[0089] Comparative Example 6
[0090] Compared with Example 2, the only difference is that the borosilicate glass powder is changed, and the glass softening point temperature is 450°C.
[0091] Comparative Example 7
[0092] Compared with Example 2, the only difference is that the borosilicate glass powder is changed, and the glass softening point temperature is 750°C.
[0093] Performance Test:
[0094] The heating paste prepared in the above-mentioned embodiment and comparative example was screen-printed on a glass substrate and sintered at 700° C. for 10 min to make a heating sheet. The following performance tests were conducted. The results are shown in Table 1:
[0095] Surface appearance: Use Zeta3D microscope to inspect the appearance of the heating element after curing.
[0096] Resistance: Use an external tester to test the line resistance.
[0097] Temperature resistance coefficient (TCR): The average resistance temperature coefficient is tested according to the national standard GB / T6148-2005 "Precision resistance temperature coefficient test method" (applicable temperature range -65℃-250℃).
[0098] Adhesion: A tensile testing machine is used to test the force required for the slurry and the glass substrate coating to break during the stretching process, which is used to indicate the adhesion of the slurry to the glass substrate (the slurry on the heating element is welded with a solder point of 1.5*1.5mm Sn(3.0)Ag(0.5)Cu as solder, the welding temperature is 260℃, and the welding method is spot welding. On the tensile testing machine, the solder point is stretched at a speed of 60mm / min at a 30° angle of the slurry. When the stretching is broken, stop immediately and measure the maximum force when the stretching breaks.
[0099] Dry-burning temperature: The temperature reached when the standard power supply is used for testing, with a constant output power of 7W and power on for 3s.
[0100] Resistance test after 30 dry burning: Use standard power supply for testing, constant output power is 7W, power on for 3s, then power off and cool naturally for 10s, that is, dry burning once. Use external meter to test line resistance after 30 dry burning.
[0101] Table 1
[0102]
[0103]
[0104] In Examples 1 to 8, the printing performance is good and the slurry coating is complete; the resistance after curing is between 0.98 and 1.62 Ω, which meets the requirements of the heating device of the electronic cigarette; the thermal resistance coefficient is relatively low, between 448 and 863, so that it has a higher heating efficiency under low power conditions, which is conducive to its application in heat-not-burn electronic cigarettes.
[0105] Examples 1 to 8 can all be heated to 100°C within 0.3s, with a fast heating rate and high heating efficiency. The dry-burning temperature can reach above 600°C. After 30 dry-burnings, the coating circuit is complete (such as Figures 2-3 ), the heating efficiency is normal. By comparing with Examples 4 to 5, it can be seen that the content of the auxiliary agent is too high, and the thickness of the heating slurry coating is too thick (such as Figures 4-5 ), the film of the heating element cracked after 4 dry-burnings; without adding additives, the film was prone to collapse (such as Figures 6-7 ), and the heating rate of the heating slurry is reduced, and the dry-burning temperature is only up to 367°C.
[0106] The thermal expansion coefficient of the heating slurry in Examples 1 to 8 matches that of the glass substrate, thereby preventing the slurry from falling off and the glass substrate from shattering during the heating and cooling process. If the borosilicate glass powder content in the heating slurry is too high, such as in Comparative Example 1, it will cause the coating to be too thick, and after multiple dry-firings, the coating will crack. If the borosilicate glass powder content is too low, such as in Comparative Example 2, the coating will fall off after the slurry is sintered and solidified. If other types of glass powder are used, such as in Comparative Example 3, the thermal expansion coefficient of the slurry does not match that of the glass substrate, and the coating will fall off and the glass substrate will shatter during the heating, solidifying and cooling process (such as Figure 8 In addition, when the glass softening point of borosilicate glass powder is 450°C, the heating paste will precipitate on the coating surface during the dry-burning test (such as Fig. 9 ), the dry-firing life of the coating becomes shorter; when the softening point of glass is 750°C, the adhesion of the heating slurry after curing is extremely low and it cannot adhere.
[0107] In summary, the heating paste suitable for the glass substrate of electronic cigarettes described in the present invention makes the thermal expansion coefficient of the heating paste match the thermal expansion coefficient of the glass substrate by selecting suitable glass powder and auxiliary agent types and contents, thereby avoiding the shedding of the paste and the breakage of the glass substrate during the heating process; the heating paste of the present invention has excellent printing performance, fast heating speed, suitable resistivity and low thermal resistance coefficient, can be heated to 100°C within 0.3s, and has been atomized for more than 300 times and dry-burned to more than 600°C. The coating circuit is complete and the heating efficiency is normal.
Claims
1. A heating slurry suitable for a glass substrate atomizing core, characterized in that: The invention comprises 5 to 35 parts by weight of a dispersion, 50 to 105 parts by weight of metal powder, 0.5 to 10 parts by weight of glass powder and 0.1 to 15 parts by weight of an auxiliary agent; Wherein, the dispersion comprises an organic solvent and a resin; The metal powder includes silver powder and palladium powder; The glass powder is lead-free borosilicate glass powder with a softening point of 600-700°C; The auxiliary agent includes at least one of mullite, zirconium dioxide or beryllium oxide.
2. The heat-generating slurry adapted for a glass substrate atomizing core according to claim 1, characterized in that: The resin is selected from at least one of acrylic resin, polymethacrylic resin, rosin resin, phenolic resin, cellulose resin or polyurethane resin; preferably at least one of cellulose resin and acrylic resin; Preferably, the cellulose resin is selected from at least one of ethyl cellulose, methyl cellulose, hydroxymethyl cellulose and carboxymethyl cellulose; preferably ethyl cellulose; Preferably, the organic solvent is selected from at least one of diethylene glycol butyl ether acetate, DBE mixed solvent, ethyl acetate, dioctyl phthalate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether, terpineol or tributyl citrate; preferably at least one of diethylene glycol butyl ether acetate, DBE mixed solvent or ethyl acetate; Preferably, in the dispersion, the mass percentage of the resin is 1 to 70%, further 5 to 50%, and further 10 to 20%.
3. The heat-generating slurry adapted for a glass substrate atomizing core according to claim 1, characterized in that: Among the metal powders, silver powder is 50 to 90 parts, preferably 60 to 80 parts; palladium powder is 2 to 15 parts, preferably 3 to 10 parts; Preferably, the silver powder comprises at least two of spherical silver powder of a first particle size, spherical silver powder of a second particle size, or flake silver powder of a third particle size; Preferably, the first particle size spherical silver powder has a particle size of 0.8-2 μm and a tap density of 3-5 g / ml; the second particle size spherical silver powder has a particle size of 100-550 nm and a tap density of 4-6 g / ml; the third particle size flake silver powder has a particle size of 0.5-1.5 μm and a tap density of 5-7 g / ml; Preferably, the silver powder comprises spherical silver powder of a first particle size and spherical silver powder of a second particle size; the mass ratio of the spherical silver powder of the first particle size to the spherical silver powder of the second particle size is (30-70):(10-30), preferably (45-60):(10-25); Preferably, the silver powder comprises spherical silver powder of the first particle size and flaky silver powder of the third particle size; the mass ratio of the spherical silver powder of the first particle size to the flaky silver powder of the third particle size is (30-70):(10-30), preferably (50-65):(10-20); Preferably, the silver powder includes spherical silver powder of the first particle size, spherical silver powder of the second particle size and flake silver powder of the third particle size, and the mass ratio of the three is (40-70):(5-30):(5-20).
4. The heat-generating slurry adapted for a glass substrate atomizing core according to claim 1, characterized in that: The particle size of the glass powder is 0.8 to 3 μm, preferably 1 to 2 μm.
5. The heat-generating slurry adapted for a glass substrate atomizing core according to claim 1, characterized in that: The auxiliary agent comprises mullite; Preferably, the mullite comprises at least one of a first particle size mullite having a particle size of 1 to 5 μm or a second particle size mullite having a particle size of 50 to 500 nm; Preferably, the mullite includes mullite of a first particle size and mullite of a second particle size, wherein the mass ratio of the mullite of the first particle size to the mullite of the second particle size is (1-9):(1-2).
6. The heat-generating slurry adapted for a glass substrate atomizing core according to any one of claims 1 to 5, characterized in that: The heating paste comprises 5 to 30 parts by weight of a dispersion, 65 to 90 parts by weight of metal powder, 1 to 7 parts by weight of glass powder and 2 to 10 parts by weight of an auxiliary agent; Preferably, the heat-generating slurry adapted for the glass substrate atomizing core further comprises a surfactant; Preferably, the surfactant comprises at least one of polyether siloxane or acrylate; Preferably, the weight portion of the surfactant is less than or equal to 5 parts, further less than or equal to 2 parts.
7. A method for preparing a heat-generating slurry suitable for a glass substrate atomizing core according to any one of claims 1 to 6, characterized in that: The dispersion is obtained in advance, and then the components are mixed.
8. An application of the heat-generating slurry adapted to a glass substrate atomizing core according to any one of claims 1 to 6, characterized in that: The atomizer core is prepared by coating the atomizer core on a glass substrate and then curing the atomizer core. Preferably, the glass substrate atomizer core is used to prepare an electronic cigarette.
9. A glass substrate atomizing core, characterized in that: It comprises a glass substrate and a heating layer coated thereon, wherein the heating layer is formed by curing the heating slurry suitable for the glass substrate atomizing core according to any one of claims 1 to 6.
10. An electronic cigarette, characterized in that: The invention comprises the glass substrate atomizing core as claimed in claim 9.
